(3fcJ eSJMSfI aj GdNjd hSjGSJgG hCeQGVgG hYdGLgGs
(3ChdgG (B:s
(3hCeG NOeI GdSGjS dgG , CYfi GdOhGH cGag hGdNjd NGUg s
(3hLOJ JYGdjbg HNW GdSdWGf Gdedc GdeLGgO Ydi Hf OGhO Hf jhSa Hf YeQ GHf QShd (B721-764 (3hGdedc GdeDjO OGhO Hf jhSa Hf YeQ Hf QShd (B696-721(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B36 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI chHQjdi HGSJGfHhd (B(1225) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs